Clinical Outcomes in Maximum Tolerated Medical Therapy in Penetrating Keratoplasty for Bullous Keratopathy - Wy, Seoyoung; Kim, Young Kook; Jeoung, Jin Wook; Kim, Mee Kum (Frontiers in Medicine, 2022)
Purpose To compare the clinical outcomes of Maximum Tolerated Medical Therapy (MTMT) in patients with penetrating keratoplasty (PKP) with those of Ahmed glaucoma valve (AGV) implantation. Methods The medical records were retrospectively reviewed in patients who had undergone PKP for bullous keratopathy and were treated with MTMT or AGV implantation for the management of glaucoma. A total of 18 bullous keratopathic patients were investigated between January 2010 and February 2017: 9 patients treated with MTMT and 9 patients treated with AGV implantation. Non-corrected visual acuity (NCVA), intraocular pressure (IOP), endothelial cell density (ECD), hexagonality, coefficient of variation (CV), central corneal thickness (CCT), median survival time of the graft and the presence of epithelial keratopathy were compared between the groups at each time point or between baseline and after treatment of glaucoma in each group. Results There were no significant differences in visual acuity and corneal thickness between the two groups or within each group over time. Both groups showed significant reduction in IOP compared with baseline IOP, and IOP reductions were greater in the AGV group than in the MTMT group (P=0.040). Significant ECD reductions were found in each group between baseline and 6 months (P=0.008 in MTMT group, P=0.015 in AGV group); however, no differences were found between the two groups until 12 months. Significant hexagonality reduction was found in the AGV group between baseline and 12 months (P=0.018). The median survival time showed no significant difference in survival analysis. Conclusions MTMT in penetrating keratoplasty for bullous keratopathy seems to similarly affect endothelial cell density or graft survival when compared with at least 12 month-followed Ahmed glaucoma valve implantation.